Cerebellar haemorrhage mimicking acute peripheral vestibulopathy: the role of the video head impulse test in differential diagnosis - ARMATO, E. (Pacini Editore SpA, 2014)
Dizziness and vertigo without neurological signs are typically due to a peripheral vestibular disease. Although the most common causes are benign, differential diagnosis must include potentially life-threatening central diseases such as cerebrovascular pathologies. A systemic clinical approach needs a careful work-up, bedside examination and appropriate instrumental investigation. The head impulse test (HIT) allows qualitative clinical assessment of canalar function; it has some limitations such as subjective evaluation, mainly in patients with a spontaneous nystagmus. A new device has been recently developed consisting of an infrared video camera (video-HIT) to provide quantitative instrumental assessment of the high-frequency vestibular-ocular reflex (VOR) gain. By reporting a case of cerebellar haemorrhage mimicking an acute peripheral vestibulopathy, the authors suggest that video-HIT may be considered a useful tool in differential diagnosis between vestibular neuritis and cerebellar vascular disease in patients with severe acute vertigo without central signs.